Self‐recovery and fatigue of double‐network gels with permanent and reversible bonds. Issue 8 (12th February 2019) - Drozdov, Aleksey D.; Christiansen, Jesper deClaville; Dusunceli, Necmi; Sanporean, Catalina‐Gabriela
ABSTRACT: Double‐network (DN) gels subjected to cyclic deformation (stretching up to a fixed strain followed by retraction down to the zero stress) demonstrate a monotonic decrease in strain with time (self‐recovery). Observations show that the duration of total recovery varies in a wide interval (from a few minutes to several days depending on composition of the gel), and this time is strongly affected by deformation history. A model is developed for the kinetics of self‐recovery. Its ability to describe stress–strain diagrams in cyclic tests with various periods of recovery is confirmed by comparison with observations on several DN gels. Numerical simulation reveals pronounced enhancement of fatigue resistance in multi‐cycle tests with stress‐ and strain‐controlled programs when subsequent cycles of deformation are interrupted by intervals of recovery. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2019, 57, 438–453 Abstract : Double‐network (DN) hydrogels with chains bridged by covalent crosslinks and reversible physical bonds demonstrate the self‐recovery phenomenon: a pronounced decay in residual strain after cyclic deformation. Depending on the type of permanent and temporary bonds, the duration of total recovery varies in a wide interval, and the reduction of residual strain with time reveals exponential and non‐exponential kinetics. Constitutive equations are developed for self‐recovery of double‐network gels to describe these observations. The model is applied to analyze the interaction between self‐recovery and fatigue under multi‐cycle loadings of DN gels.